Long-Term Care over an Uncertain Future: What Can Current Retirees Expect? - Peter Kemper; Harriet L. Komisar; Lisa Alecxih (SAGE Publishing, 2005)
The leading edge of the baby boom generation is nearing retirement and facing uncertainty about its need for long-term care (LTC). Using a microsimulation model, this analysis projected that people currently turning age 65 will need LTC for three years on average. An important share of needed care will be covered by public programs and some private insurance, but much of the care will be an uninsured private responsibility of individuals and their families-a responsibility that will be distributed unequally. While over a third of those now turning 65 are projected to never receive family care, three out of 10 will rely on family care for more than two years. Similarly, half of people turning 65 will have no private out-of-pocket expenditures for LTC, while more than one in 20 are projected to spend $100,000 or more of their own money (in present discounted value). Policy debate that focuses only on income security and acute care-and the corresponding Social Security and Medicare programs-misses the third, largely private, risk that retirees face: that of needing LTC.